1987
DOI: 10.1063/1.98102
|View full text |Cite
|
Sign up to set email alerts
|

Development of a formed-ferrite flash plasma light source for gas laser applications

Abstract: A new type of plasma light source using amorphous filaments formed on ferrite substrates has been developed for application to gas laser excitation and preionization. A formed filament acts as a leading guide to produce a long-distance, high-current discharge plasma which emits hard ultraviolet photons. The plasma production mechanism and technological advantages over conventional ways of producing plasmas of the formed-ferrite flash are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A 0 transition. [18][19][20][48][49][50][51][52][53][54] Because of the D X excitation sources utilized-electric discharges, lamps with monochromators, ArF lasers-it was impossible to achieve single vibrational level resolution in the excitation of the D state. The measurements were performed under multiple-collision conditions and the kinetic analysis utilized a onelevel approximation.…”
Section: Introductionmentioning
confidence: 99%
“…A 0 transition. [18][19][20][48][49][50][51][52][53][54] Because of the D X excitation sources utilized-electric discharges, lamps with monochromators, ArF lasers-it was impossible to achieve single vibrational level resolution in the excitation of the D state. The measurements were performed under multiple-collision conditions and the kinetic analysis utilized a onelevel approximation.…”
Section: Introductionmentioning
confidence: 99%
“…At x=7 cm it is ~4о , and a little wider in from of discharge. It is probably due to structural damage to ferrite surface (as described in [2], it becomes amorphous) during discharge along a specified path. Change in structure as well as increased roughness lead to increased dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…The photos demonstrated that the path didn't deform throughout all of the experiments described in this work and that the discharge always stayed right on it. More in depth description of the discharge propagation mechanism along the conductive path over ferrite surface was described in [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, formed-ferrite surface discharges 9 have attractive features: a very simple and relatively compact system, the possibility of a pulseperiodic operating regime, and a relatively low operating voltage. [9][10][11] This photolysis light source has been used in the present work to drive and study the XeF(C -A) laser.…”
mentioning
confidence: 99%